Compared study to the effectiveness of the physical education lesson between AL Karakh education first and second in Baghdad Governorate - Emad, Thamer (Journal of Physical Education, 2019)
Education relies on the development of students and raise the cognitive and emotional potential and psychomotor through the curriculum, which should be characterized by inclusiveness and integration, which is a physical education lesson is an important part of the curriculum, as students from which he can achieve many of the goals of the school curriculum mental, physical and psychological integration and stimulate the effectiveness of achievement, innovation and creativity through the application vocabulary lesson optimally, and taking on the responsibility of the educational administration of the school to provide all administrative, physical and financial resources allocated to them and the places and support the teaching staff specialized in the success of the educational process and to achieve the lesson effectively. Despite continuing calls urging to activate the role of school sports, but that there are weak in their application, and through access to the reality of some of the schools of the province of Baghdad and direct contact with teachers specialization athlete, who often complain of the lack of material and financial resources as well as the differentiation of other subjects and exploitation assigned to study the breeding of sport in complete curriculum times, which helped in the weakness of physical activity. It is therefore to be standing on the effectiveness of the physical education lesson and the availability of the necessary criteria to its success and the degree of applicability in AL Karakh education first and second schools of the province of Baghdad during the school year. It was developed a questionnaire to get to know the criteria on the degree of effectiveness of the application of physical education lesson and differences in degrees applied to schools of Baghdad's AL Karakh education first and second. The research sample was from the school of specialize in sports averages and junior high school identification of these districts. It was addressed to the group of the concepts of the effectiveness of physical education lesson and the role of school administrations in supporting them on according to the objectives of physical education lesson to be met, and the duties of the teacher in the activation of this lesson, and the obstacles that prevent it, as well as the use of previous studies that touched on the subject. To achieve the objectives of the study used a descriptive approach to suitability and the nature of the problem, select the study population was selected sample of which amounted to 123 teachers, spread over AL Karakh education first and second, according to the percentage-based (30%). Been developed questionnaire included (5) axes, and formulated a set of paragraphs function by (56) items and distributed them according to the views of accredited experts and the percentage of agreement on the validity of (80%) for the virtual sincerity, and the degree of stability through Cronbach's alpha equation, which amounted rate (0.946), a high percentage of expressing the stability of the paragraphs of the questionnaire the existence of consistency and accuracy in the tool. The questionnaire was distributed to a sample study in confined period between 24.03.2016 until 18.05.2016. And adopted the (spss) statistical Pouch in the treatment of the results. Questionnaire axes have shown (non-function) as the real moral of the larger (0.05), which indicates that the application of physical education lesson effectively. Moreover, there did not show significant differences between them, as the two parties based on the same rules and regulations and finances, which showed a lack of success of the effectiveness of the application optimally. The conclusions of the study show the weakness of orthodontic device and standards necessary for that, and the lack of possibilities available to activate it. The study recommended taking into consideration the views of beneficiaries on an ongoing basis to support and develop school sports, and the adoption of a dedicated their curricula like other subjects, prodding the posts and integration with counterparts to improve relations and communication for the exchange of cultures and sports experiences on a regular basis.